Indigenous Lien Minh chicken of Vietnam: Phenotypic characteristics and single nucleotide polymorphisms of GH, IGFBP and PIT candidate genes related to growth traits - Huong Do Thi Thu; NGUYEN TRAN THI BINH; LUC DO DUC; DOAN BUI HUU; DANG THUY NHUNG; CANH NGUYEN XUAN; LINH NGUYEN VIET; ANH NGUYEN THAI; MINH LUU QUANG; DANG KIM PHAM; Hoang Thinh Nguyen (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Thu HDT, Binh NTT, Duc LD, Huu DB, Nhung DT, Xuan CN, Viet LN, Thai AN, Quang ML, Pham DK, Hoang TN. 2020. Indigenous Lien Minh chicken of Vietnam: Phenotypic characteristics and single nucleotide polymorphisms of GH, IGFBP and PIT candidate genes related to growth traits. Biodiversitas 21: 5344-5352. Lien Minh chicken, a Vietnamese indigenous breed, has contributed importantly to the economic development of rural citizens in Cat Ba island, Hai Phong province due to its highly desired characteristics. However, Lien Minh chickens showed a slower growth rate when compared to other industrial chicken breeds. Therefore, the study aims at assessing the appearance characteristics and growth performance of 100 individuals Lien Minh chickens, and investigating the single nucleotide polymorphisms (SNPs) of candidate genes including GH, IGFBP and PIT, which might be associated with growth traits. Blood samples were collected from wing of Lien Minh chickens and used for DNA extraction. Genotyping by the PCR-RFLP method was then conducted. The allele frequencies were 0.97 and 0.03 for alleles A and G of GHi3 gene, respectively. For in IGFBP2 gene, allele frequencies were found as 0.47 for the A allele and 0.53 for G allele. The allele frequencies for PIT1 gene were recorded as 100% for allele B. These polymorphic loci (GHi3, PIT1, and IGFBP2) were followed by the Hardy-Weinberg equilibrium in the Lien Minh chicken population. These were the initial results, which could be used to analyze the correlation of molecular markers and growth traits in Lien Minh chickens.